Penguatan Literasi Digital Dalam Pembelajaran Bahasa Inggris Bagi Guru-Guru TK - Ermy Dikta Sumanik; Axelon Samuel Renyaan; Andrijanni (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Improving teacher competence is very important to support the quality of education. There is still a lack of digital literacy mastery among kindergarten teachers in learning, especially learning English. There are many obstacles faced by teachers in mastering digital literacy such as a lack of knowledge about the features of laptops, and lack of understanding how to operate laptops or smartphones. The other obstacles in learning English in kindergarten is the teachers educational background who are not from the English Education study program. The purpose of this Community Partnership Service Activities is to improve the teacher competence in mastering ICT. The method used is through training, question and answer and direct mentoring. Participants who participated in this activity were kindergarten teachers from cluster 3 of Jayapura city consisting of 12 kindergarten teachers. This activity conducted for two days. At the beginning of the activity, a pre-test was distributed to measure participants' understanding of digital literacy in learning English. Monitoring and evaluation are done by giving post-test directly to participants. The results of this this Community Partnership Service Activities are 82% or 10 teachers from 12 teachers have increased their competence in mastery of digital literacy in learning English in kindergarten.